Comparison Of Life-Cycle Impacts Between Compressed Brick And Fired Brick: Impact 2002+ Method - Ching, Liang Yi (2022)
Fired bricks and compressed bricks are common construction material produced and applied worldwide since the early days. However, negative environmental impacts generated during brick manufacturing process are inevitable. In this setting, utilisation of life cycle assessment (LCA) to examine life cycle environmental implications of fired brick and compressed brick is preferable. Several studies have conducted LCA on various construction materials, including fired brick and compressed brick. However, limited research has been conducted to compare their environmental effects using Impact 2002+ methodology. The aim of this study was to evaluate and to make comparison on the environmental impacts of compressed brick and fired brick using Impact 2002+ method. Functional unit was set to 1 kg of bricks and the scope was limited to cradle-to-gate analysis. Ecoinvent database allocation at point of substitution (APOS) model was used to extract data for analysis. Fired brick and compressed brick mix proportions were obtained from existing literature. All Impact 2002+ endpoint categories and selected midpoint categories such as aquatic acidification, human toxicity and ozone layer depletion were analysed and discussed. The results have indicated that compressed brick is better for the environment compared to fired brick since it has lesser environmental implications in endpoint and midpoint categories. Furthermore, compressive strength and cost for both brick types are evaluated. It is found that both brick types can satisfy the minimum compressive strength requirement, but compressed brick comes at a lower cost. Compressed brick is recommended to be used since it is a more sustainable and cost-effective option, while fulfilling minimum strength requirement.